(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The geometrical characteristics of one of the NK (′′ Nearly Kahler ′′)manifold structures are provided by M, where M represents for the Nearly kahler manifold, and the MProjective Curvature Tensor In this work, we study the properties of a virtually kahler manifold. Important findings of the study include the following: - It was shown that this tensor had the standard properties of Riemannian curvature symmetry. Projective tensor (M- tensor) components to be calculated for the NK manifold. Links between this manifold’s tensor components were created after certain observations were made